Новите морални вредности во современите политички процеси - Донев, Дејан (Konrad-Adenauer-Stiftung, Skopje, 2006)
The relation between politics and ethics is persistent human problem that beside meaning disability for mutual exclusion, means also an formulation and practice of a new kind of political ethics – ethics of responsibility according to which every body must take care for the consequences of his own steps in political. In our time, here and now, in transition, after the fall of undemocratic, authoritative, one party, socialistic paradigm, the democracy means getting back the politics to the people. In another words it means responsibility (moral), knowledge, ability, criticism of the elected representatives, and also, as Cant said, "democratic age of the people", true representation of the politicians for the common wealth and human values: Freedom, Peace, Justice, Equality, Human rights, with no privileges, self-affirmation, group egoism, manipulation, with no misuse of the peoples welt fare. In the same time, the meaning and the importance of the ethics for every body and any profession, including politics, is consist of repeatedly consideration of the importance of the profession, as from responsible taking care for the consequences of human professional acting and his human value and human acting.
The new moral values in politics
Keywords: вистина, морална политика, етика на одговорноста